Relationships between plasma levels of nitrogenous metabolites and some psycho-neuro-endocrine parameters - Bombushkar, Igor; Gozhenko, Anatoliy; Korda, Mykhaylo; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. It was recently shown by our group that bilirubin has a neurotropic activity. It is also shown that endogenous uric acid exerts a noticeable modulating effect on neuro-endocrine adaptation factors. In this study, we supplemented the constellation both of subjects of influence with other nitrogenous metabolites - urea and creatinine, and the objects of influence - with plasma levels of the main adaptation hormones and the severity of trait and reactive anxiety. Materials and Methods. The object of observation were almost healthy volunteers: 30 females (30÷76 y) and 31 males (24÷69 y). In basal conditions determined plasma levels of nitrogenous metabolites as well as cortisol, aldosterone, testosterone, triiodothyronine and calcitonin, estimated the severity of the trait and reactive anxiety, recorded the ongoing HRV and EEG. After 4 or 7 days, repeated testing was performed. Results. By constructing regression models, it was found that direct bilirubin determines the levels of psycho-neuro-endocrine parameters by 66,0%, free bilirubin by 56,7%, uric acid by 40,8%, creatinine by 37,6%, and urea - by 31,1%. Taken together, nitrogenous plasma metabolites determine the severity of trait, but not reactive anxiety, plasma levels of testosterone, cortisol and triiodothyronine, but not calcitonin and aldosterone, as well as a number of HRV and EEG parameters by 70,6%. Conclusion. Nitrogenous plasma metabolites, even in the absence of uremia, are able to influence the state of the psyche, autonomic and central nervous and endocrine systems, apparently through aryl hydrocarbon and adenosine receptors of neurons and endocrinocytes and/or directly.